2017
DOI: 10.1093/humrep/dex258
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of occult leiomyosarcomas and atypical leiomyomas after laparoscopic morcellation of leiomyomas in reproductive-age women

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…If our study design was based on a single MIS unit or MIS procedures only, we would have found no occult LMS cases as well as no occult LMS in women of reproductive age. Indeed, a recent case series of laparoscopic myomectomies in women of reproductive age reported no cases of LMS morcellation [16]. Based on these results and a recently suggested algorithm [18] for the use of power morcellation, one can suppose that morcellation in young women is very safe.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…If our study design was based on a single MIS unit or MIS procedures only, we would have found no occult LMS cases as well as no occult LMS in women of reproductive age. Indeed, a recent case series of laparoscopic myomectomies in women of reproductive age reported no cases of LMS morcellation [16]. Based on these results and a recently suggested algorithm [18] for the use of power morcellation, one can suppose that morcellation in young women is very safe.…”
Section: Discussionmentioning
confidence: 88%
“…Thus, selection of specific centers and units (such as Gynecologic Oncology units) can overestimate the prevalence due to the higher-risk population treated. On the other hand, selected reports from only laparoscopic procedures or from only MIS centers may indicate a lower prevalence of occult LMS or risk of power morcellation [14][15][16] than multicenter studies [17].…”
Section: Discussionmentioning
confidence: 99%
“…For patients undergoing myomectomy or hysterectomy, there was a warning, in April 2014, against the use of laparoscopic power morcellation by the FDA ( 8 ). Unexpected malignancy was estimated to occur in 1 out of 350 women ( 8 , 9 , 10 , 11 ). After this warning, several renowned hospitals across the world stopped using EMM.…”
Section: Introductionmentioning
confidence: 99%
“…Population‐based estimates of the incidence of uterine sarcoma range from 1.55 to 1.95 per 100 000 women per year. It is estimated that 0.1–0.3% of patients operated on for presumed uterine leiomyoma have a uterine sarcoma.…”
Section: Introductionmentioning
confidence: 99%